An Examination of Corporate Capital Structure Decisions in the Context of the United Kingdom - Hui, Kiki (2009)
This study attempts to investigate the determinants of capital structure of a sample of 136 listed firms on the FTSE 350 Index in the United Kingdom from year 1994 to 2008. In doing so, a correlation matrix is run in order to separate a set of significant factors influencing the capital structure from the list of the following independent variables: assets structure, profitability, liquidity, growth opportunities, firm size, product uniqueness, business risk, non-debt tax shields, free cash flow. As a result of the Hausman test, fixed effects regression is then conducted in order to examine the relationship between capital structure and its potential determinants. The evidence generally suggests that asset structure, profitability, liquidity, growth opportunities, firm size, product uniqueness and non-debt tax shields are factors in influencing debt-equity ratios of firms in UK in this study; in contrast, business risk does not have any explanation power for UK firm’s financing choices.